PENGARUH PEMANFAATAN TEPUNG DAUN INDIGOFERA (Zollingeriana) TERHADAP PENAMPILAN PRODUKSI KELINCI NEW ZEALAND WHITE JANTAN - Muhamad Syafi'i; Supranoto; Fani Evadewi; Wida Nurnaningsih (Fakultas Peternakan. Unwiku, Purwokerto, 2025)
This study aims to evaluate the effect of Indigofera leaf flour (Zollingeriana) on the production performance of male New Zealand White (NZW) rabbits.Twenty male NZW rabbits aged ± 2 months were fed with 4 treatments: 0%, 10%, 20%, and 30% Indigofera leaf flour in the diet.The research results showed no significant differences (p > 0.05) in Daily Body Weight Gain (PBBH) and Dry Matter Intake (BK) among the groups.However, numerically, the addition of 20% Indigofera tends to increase Daily Body Weight Gain (PBBH) and Dry Matter Intake (BK).Indigofera up to 30% in the feed still maintains rabbit production performance.Further research is needed to optimize the use of Indigofera as an alternative feed for rabbits